Making the mummies dance inside the Metropolitan Museum of Art - Hoving, Thomas 1931-2009 (Simon & Schuster, 1993)
No museum in the world is like the Metropolitan Museum of Art -- and no man has ever run it, or revolutionized it, like Thomas Hoving. From seducing important patrons like Robert Lehman, Nelson Rockefeller, Walter Annenberg, and Brooke Astor to spiriting ancient treasures across international borders; from striking secret agreements with the world's most powerful dealers to sidestepping rivals; from securing blockbuster exhibitions such as "Tut" to seizing the most phenomenal Velazquez portrait, in a decade Hoving shook the institution out of royal repose and transformed it into the most vital cultural presence in the country.